Hair Mercury Levels Detection in Fishermen from Sicily (Italy) by ICP-MS Method after Microwave-Assisted Digestion. (5th April 2016) - Giangrosso, Giuseppe; Cammilleri, Gaetano; Macaluso, Andrea; Vella, Antonio; D'Orazio, Nicolantonio; Graci, Stefania; Lo Dico, Gianluigi Maria; Galvano, Fabio; Giangrosso, Margherita; Ferrantelli, Vincenzo
Abstract : A number of ninety-six hair samples from Sicilian fishermen were examined for total mercury detection by an Inductively Coupled Plasma Mass Spectrometry (ICP-MS) method. The mercury levels obtained were compared with mercury levels of 96 hair samples from a control group, in order to assess potential exposure to heavy metals of Sicilian fishermen due to fish consumption and closeness to industrial activities. Furthermore, the mercury levels obtained from hair samples were sorted by sampling area in order to verify the possible risks linked to the different locations. The overall mean concentration in the hair of the population of fishermen was6.45 ± 7.03   μ g g −1, with a highest value in a fisherman of Sciacca (16.48  μ g g −1 ). Hair mercury concentration in fishermen group was significantly higher than in control group (p < 0.01 ). There was no significant difference in hair total mercury concentrations between sampling areas (p > 0.05 ). The results of this study indicate a greater risk of exposure to mercury in Sicilian fishermen, in comparison to the control population, due to the high consumption of fish and the close relationship with sources of exposure (ports, dumps, etc.).